The dreadful word: speech crime and polite gentlemen in Massachusetts, 1690-1776 - Olbertson, Kristin A. (Studies in legal history, 2022)
Introduction -- A politer peace -- Sensibility -- Civility -- Credibility -- Cacophony -- Respectability.